Dichlorido(2-{[2-(piperazin-4-ium-1-yl)ethyl] iminomethyl}phenolate)cadmium(II) - Salga, M.S.; Khaledi, H.; Ali, H.M. (International Union of Crystallography, 2010)
In the title compound, [CdCl(2)(C(13)H(19)N(3)O)], the Cd(II) ion is pentacoordinated with the N,N,O-tridentate Schiff base 2-{[2-(piperazin-4-ium-1-yl)ethyl] iminomethyl} phenolate ligand and two Cl atoms in a highly distorted square-pyramidal geometry; the piperazine ring adopts a chair conformation. In the crystal structure, adjacent molecules are linked together via N-H center dot center dot center dot O and N-H center dot center dot center dot Cl hydrogen bonds, forming infinite layers parallel to the ab plane. The layers are further connected through C-H center dot center dot center dot Cl interactions into a three-dimensional network.